EFFECT OF DIFFERENT CONCENTRATION OF POULTRY DROPPINGS ON THE GROWTH AND PROXIMATE COMPOSITION OF Amaranthus cruentus L. - ABUBAKAR, ABDURRAHMAN; EMMANUEL MBAYA, DAUDA; ADAMU, MOHAMMED (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Amaranthus cruentus L. is a leafy vegetable commonly grown in Nigeria and other West African countries. Due to its high demand and abundance of poultry manure, farmers abuse the usage of poultry manure thereby causing soil nutrient imbalance and associated animal and human health risks, as well as surface water and groundwater contamination. This study investigated the growth performance, yields, and nutritional quality of Amaranthus cruentus under different concentration of poultry manure. Four different concentrations were used as treatments including 5, 10, 15, and 20 kg/plot, while plot without the application of poultry manure served as the control. It was observed that the growth parameters, such as plant height, stem girth, number of leaves and leaf area of plants have significantly affected by the increase in the concentration of the poultry manure. Optimum growth and significant improvement in the proximate composition such as ash and moisture content, fat, crude protein and fiber was achieved in poultry manure concentration of 15 kg/plot relative to the other treatments. Further increase of the poultry manure to the concentration of 20 kg/plot even though increase the growth performance, but lowered the available carbohydrate and total energy. Hence, the research recommended for farmers the use of 15 kg/plot of poultry manure for an enhanced/higher growth of A. cruentus.